Analysis of Role of Haematological Parameters in Diagnosis of Grampositive and Gram-negative Urinary Tract Infection: A Case-control Study - Sudha Srinivasan; Ayeesha Sithika Thajudeen; Kundhavai Chandrasekaran; Vijayashree Raghavan; D Roshini (Journal of Clinical and Diagnostic Research)
Introduction: Urinary Tract Infections (UTIs) are a prevalent global health issue, primarily caused by bacterial infections. Early diagnosis and intervention are critical to preventing complications like pyelonephritis and mitigating the risk of recurrent infections that can lead to permanent scarring. Aim: To investigate the haematological parameters in patients with confirmed UTIs, comparing them with non UTI counterparts and discerning variations in haematological parameters between UTIs caused by gram-positive and gram-negative bacterial organisms. Materials and Methods: This prospective case-control study was conducted at Chettinad Hospital and Research Institute (tertiary care centre), Chengalpattu, Tamil Nadu, India between January 2023 and July 2023, included 105 culture-positive UTI cases and 105 age- and gender-matched culture-negative controls. Cases included patients over 12 years of age with confirmed UTIs, while exclusions for both groups included pregnancy, individuals under 12 and those with haematological disorders. Controls were also excluded if they had diabetes or chronic kidney disease. Urine cultures on blood and MacConkey agar identified pathogens such as E. coli, Pseudomonas, Klebsiella, Enterobacter, Proteus and Citrobacter. Gram-positive isolates included Enterococci species, Staphylococcus aureus and Staphylococcus saprophyticus. Haematological parameters such as Haemoglobin (Hb), White Blood Cell Count (WBC), platelet count, Mean Platelet Volume (MPV), Red Cell Distribution Width (RDW), Platelet Distribution Width (PDW) and Plateletcrit (PCT) were analysed using an automated haematology analyser. Statistical analysis was performed using Statistical Package for Social Sciences (SPSS) software version 22.0 with significance set at p-value <0.05. Results: The UTI patients exhibited lower Hb and higher WBC, platelet count, MPV, RDW, PDW and PCT compared to controls. Gram-positive UTI infections showed higher WBC count, platelet counts, RDW, PDW and PCT, but lower MPV compared to gram-negative UTI infections. E. coli and Enterococcus were the predominant gram-negative and gram-positive pathogens, respectively, reflecting distinct haematological profiles. These results highlight distinct immune and haematological profiles in UTI patients, depending on the infecting organism. Conclusion: The UTI patients exhibited lower Hb and higher WBC, platelet count, MPV, RDW, PDW and PCT compared to controls. Gram-positive UTI infections showed higher WBC count, platelet counts, RDW, PDW and PCT, but lower MPV compared to gram-negative UTI infections. E. coli and Enterococcus were the predominant gram-negative and gram-positive pathogens, respectively, reflecting distinct haematological profiles. These results highlight distinct immune and haematological profiles in UTI patients, depending on the infecting organism.